Effect of alcohol on diesel engine combustion operating with biodiesel-diesel blend at idling conditions - H. M., Mahmudul; Hagos, F. Y.; M. Mukhtar, N. A.; R., Mamat; Abdul Adam, Abdullah (IOP Publishing, 2018)
Biodiesel is a promising alternative fuel to run the automotive engine. However, its blends have not been properly investigated during idling as it is the main problem to run the vehicles in a big city. The purpose of this study is to evaluate the impact of alcohol additives such as butanol and ethanol on combustion parameters under idling conditions when a single cylinder diesel engine operates with diesel, diesel-biodiesel blends, and diesel biodiesel-alcohol blends. The engine combustion parameters such as peak pressure, heat release rate and ignition delay were computed. This investigation has revealed that alcohol blends with diesel and biodiesel, BU20 blend yield higher maximum peak cylinder pressure than diesel. B5 blend was found with the lowest energy release among all. B20 was slightly lower than diesel. BU20 blend was seen with the highest peak energy release where E20 blend was found advance than diesel. Among all, the blends alcohol component revealed shorter ignition delay. B5 and B20 blends were influenced by biodiesel interference and the burning fraction were found slightly slower than conventional diesel where BU20 and E20 blends was found slightly faster than diesel So, based on the result, it can be said that among the alcohol blends butanol and ethanol can be promising alternative at idling conditions and can be used without any engine modifications.